(untitled) (Al-Aasar, 2025)
This article explores the significance of spending in Allah’s way, emphasizing its role in aligning human capabilities with divine consent and promoting the welfare of humanity. Drawing from 14 pages, 6839 words, 23 Quranic references, 19Ahadith, and the poetry of Dr. Allama Muhammad Iqbal, it underscores the spiritual and economic benefits of generosity and the detrimental effects of close-fistedness. Spending in Allah’s way reflects strong faith in Allah and His Prophet (peace and blessings be upon him), while miserliness incurs divine displeasure and hinders economic growth. Generosity boosts public purchasing power, sustains businesses, and fosters progressive economies, whereas tightfistedness leads to economic stagnation and diminishes one’s good deeds. The article also outlines the manners and conditions of charitable spending, highlighting its spiritual and societal impact. A poignant dialogue between a man and Allah on the Day of Judgment is presented, illustrating the eternal significance of these acts. The all contents consist Islamic teachings and principles.